Effect of salinity and drip fertigation on maize (Zea mays) and water use efficiency - GOVADA, DIVYA SREE; A, MRUDHULA K; M, SUNIL KUMAR; G, RAMESH; G, KISHORE BABU; BSS, SIDDARTHA NAIK (The Indian Journal of Agricultural Sciences, 2024)
Climatic variability is immensely pressurised on freshwater availability in arid and semi-arid ecosystems, leading to poor quality water for crop production not becoming uncommon, especially in coastal ecosystems. A field experiment was conducted during winter (rabi) season of 2022–23 at the Saline Water Scheme at Agricultural College Farm, Acharya N. G. Ranga Agricultural University, Bapatla, Andhra Pradesh to assess the impact of saline water on maize growth, yield and water use efficiency under drip fertigation. The experiment consisted 8 treatments laid in randomized block design (RBD) with 4 replications. The utilization of the BAW irrigation method, together with the application of a prescribed quantity of fertilizer, resulted in the highest plant height and dry matter accumulation during all phases of crop growth. These outcomes were comparable to those achieved by using a combination of fresh water and saline water with an electrical conductivity of 2 dS/m. The maximum values for the number of kernels per cob (451), cob length (17.2 cm), cob weight (164.4 g), kernel yield (7.38 t/ha), stover yield (9.61 t/ha) and water use efficiency (18.5 kg/ha mm) of maize were observed under the irrigation treatment T4. The parameters exhibited their minimum values when irrigation was conducted using water with a salt level of 4 dS/m and no fertilizers were used. However, there was no statistically significant difference observed in the number of cobs per plant and harvest index of maize when saline water was used in conjunction with drip fertigation. In the context of maize cultivation, employing a cyclic irrigation technique that alternates between salty (EC 2–4 dS/m) and freshwater sources, in conjunction with recommended dose of fertiliser (RDF) has the potential to deliver comparable crop development, productivity, and economic benefits when compared to the use of freshwater sources alone.